Dyslexia Candidate Gene and Ciliary Gene Expression Dynamics During Human Neuronal Differentiation - Bieder, Andrea; Yoshihara, Masahito; Katayama, Shintaro; Krjutškov, Kaarel; Falk, Anna ; 0000-0003-1634-8610; Kere, Juha; Tapia-Páez, Isabel (Molecular Neurobiology, 2020)
Developmental dyslexia (DD) is a neurodevelopmental condition with complex genetic mechanisms. A number of candidate genes have been identified, some of which are linked to neuronal development and migration and to ciliary functions. However, expression and regulation of these genes in human brain development and neuronal differentiation remain uncharted. Here, we used human long-term self-renewing neuroepithelial stem (lt-NES, here termed NES) cells derived from human induced pluripotent stem cells to study neuronal differentiation in vitro. We characterized gene expression changes during differentiation by using RNA sequencing and validated dynamics for selected genes by qRT-PCR. Interestingly, we found that genes related to cilia were significantly enriched among upregulated genes during differentiation, including genes linked to ciliopathies with neurodevelopmental phenotypes. We confirmed the presence of primary cilia throughout neuronal differentiation. Focusing on dyslexia candidate genes, 33 out of 50 DD candidate genes were detected in NES cells by RNA sequencing, and seven candidate genes were upregulated during differentiation to neurons, including DYX1C1 (DNAAF4), a highly replicated DD candidate gene. Our results suggest a role of ciliary genes in differentiating neuronal cells and show that NES cells provide a relevant human neuronal model to study ciliary and DD candidate genes.
Keywords: Cilia/genetics; Dyslexia/genetics; Gene Expression; Gene Expression Regulation; Humans; Induced Pluripotent Stem Cells/cytology; Neural Stem Cells/metabolism; Neurogenesis/genetics; Neurons/metabolism